Inovasi Rocket Stove Beres (Bakar Efisien, Ramah, dan Emisi Sedikit) sebagai Solusi Pengelolaan Sampah Anorganik Minim Asap - Isni Lailatul Maghfiroh; Ahmad Abdullah Fahmi; Acha Fadila Putri; Khofifatuz Zaini; Chanda Nurul Fadhila; Nadhaturrahma Cahaya Sabita; Eka Wulan Ndari (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
The BERES (Efficient, Friendly, and Low Emission) Rocket Stove innovation is presented as a solution for managing inorganic waste that emphasizes combustion efficiency and environmental friendliness with minimal smoke emissions. This study aims to develop and test the performance of the BERES Rocket Stove in processing inorganic waste using an optimal combustion method so as to reduce waste volume while minimizing the impact of air pollution. The research method includes designing a prototype stove with a special configuration to ensure perfect combustion, followed by testing fuel efficiency and measuring combustion gas emissions using gas analysis equipment. The results show that the BERES Rocket Stove is capable of burning inorganic waste efficiently with lower fuel consumption compared to conventional stoves. In addition, the smoke emissions produced also decreased significantly, thus having a positive impact on the surrounding air quality. This innovation not only facilitates the management of inorganic waste at the household and small community levels, but also provides an economical and easy-to-implement environmentally friendly alternative solution. In conclusion, the BERES Rocket Stove has the potential to be an appropriate technology for effective, efficient, and sustainable inorganic waste management with minimal air pollution. This study recommends further development and widespread implementation of this technology to support waste management and environmental conservation programs